Women empowerment : an analysis from the Qur'anic perspective - Muhammad Faizul Haque (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
'Women empowerment' is perceived differently by the Western and Muslim worlds. Policymakers and society have failed to understand this concept correctly. It is very unfortunate that this concept is negatively understood in both worlds. Women are generally positioned in a specific place in the family and society and are being constantly degraded. This is due to the narrow practice of socio-cultural traditions, patriarchal social systems and misunderstanding of the sacred texts of the Qur'an and Sunnah. This research seeks to identify the nature of women empowerment from the Qur'anic and Sunnah perspectives. Further, it investigates specific issues from the Qur'anic perspective such as the position of women's rights which include participation in education, economics, politics, decision-making process and social activities. It examines the main obstacles which obstruct women empowerment in the family as well as in society. It has collected all relevant verses of the Qur'an that address the actual position and place of women in society. This research also explores how the Qur'ān addresses the current issue and provides the guideline for women to get involved in social activities without compromising their faith, chastity and dignity. The present research adopted the inductive and analytical approaches. Under the inductive approach, the most related facts and texts have been gathered from tafsir. Whilst under the analytical approach, the most pertinent texts, the views of Qur'an interpreters (mufassirins) and Muslim jurists have been analyzed thoroughly with a view of providing solutions to overcome problems related to women empowerment. The present research has found throughout the discussion that both man and woman enjoy equal status. Most importantly, it is found that both hold an equal position in the sight of Allah (SWT) and will be treated equally in terms of receiving rewards and punishments based on their deeds, not based on their gender. The Qura'n and Prophetic traditions never position women as subordinates or inferior in the family or society. Islam recognizes women's potential and considers it as a key element that can be utilized in raising the quality of life of families and developing societies. Thus, Islamic teachings have guaranteed women's rights, positions, participation in education, economics, politics, decision-making process and social activities as well as dignity as much as men in the family and in society. Additionally, the current research provides solutions to all the challenges to women empowerment and their participation in the family and society. In order to overcome and change the people's perceptions regarding women empowerment, academicians and policymakers would benefit from the findings of this research. They would be in a better position to give women due rights and allow them genuine participation in social activities. As a result, it will bring positive impact and change to women's minds which will encourage them to utilize their potential in family matters and social responsibilities. It will also create social harmony between men and women by showing mutual gratitude and respect through understanding, preaching, counseling and advising.